The global structure of upper troposphere‐lower stratosphere ozone in GEOS‐5: A multiyear assimilation of EOS Aura data. Issue 5 (3rd March 2015) - Wargan, Krzysztof; Pawson, Steven; Olsen, Mark A.; Witte, Jacquelyn C.; Douglass, Anne R.; Ziemke, Jerald R.; Strahan, Susan E.; Nielsen, J. Eric
Abstract: Eight years of ozone measurements retrieved from the Ozone Monitoring Instrument and the Microwave Limb Sounder, both on the EOS Aura satellite, have been assimilated into the Goddard Earth Observing System Version 5 (GEOS‐5) data assimilation system. This study evaluates this assimilated product, highlighting its potential for science. The impact of observations on the GEOS‐5 system is explored by examining the spatial distribution of the observation‐minus‐forecast statistics. Independent data are used for product validation. The correlation of the lower stratospheric (the tropopause to 50 hPa) ozone column with ozonesondes is 0.99 and the (high) bias is 0.5%, indicating the success of the assimilation in reproducing the ozone variability in that layer. The upper tropospheric (500 hPa to the tropopause) assimilated ozone column is about 10% lower than the ozonesonde column, but the correlation is still high (0.87). The assimilation is shown to realistically capture the sharp cross‐tropopause gradient in ozone mixing ratio. Occurrence of transport‐driven low ozone laminae in the assimilation system is similar to that obtained from the High Resolution Dynamics Limb Sounder (HIRDLS) above the 400 K potential temperature surface, but the assimilation produces fewer laminae than seen by HIRDLS below that surface. Although the assimilation produces about 25% fewer occurrences per day during the 3 years of HIRDLS data, the interannual variability is captured correctly. This data‐driven assimilated product is complementary to ozone fields generated from chemistry and transport models. Applications include study of the radiative forcing by ozone and tracer transport near the tropopause. Key Points: Ozone observations from OMI and MLS are assimilated into GEOS‐5 Very good agreement with ozonesondes in the lower stratosphere Representation of transport‐driven ozone structures in the UTLS